1982
DOI: 10.1016/s0006-3495(82)84510-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dipolar properties of the voltage-dependent pore former alamethicin in octanol/dioxane

Abstract: Dielectric constant and loss of the membrane-active peptide alamethicin in octanol/dioxane mixtures have been measured at frequencies between 5 kHz and 50 MHz. On the basis of a rotational mechanism of dipolar orientation, the observed dispersion provides information regarding size, shape, and dipole moment of the structural entities which the solute may assume in media of diverse lipophilicity. Particularly detailed results are obtained in a pure octanol solvent where an apparent molecular weight of alamethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 12 publications
3
30
1
Order By: Relevance
“…Upon application of a sufficiently large voltage these aggregates are converted into arrays of parallel helices, which form water-filled ion conducting channels. Large dipole moments of 60-75 D have been determined for alamethicin (Schwarz & Savko, 1982;Yantorno, Takashima & Mueller, 1982) and trichotoxin A40 (Schwarz, Savko & Jung, 1983). Elementary dipoles originate from the charge separation phenomenon at peptide bonds (Hol et al, 1978) and sum up to macrodipoles in case of rods of helical structure (Hol, Halie & Sander, 1981;Hol, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon application of a sufficiently large voltage these aggregates are converted into arrays of parallel helices, which form water-filled ion conducting channels. Large dipole moments of 60-75 D have been determined for alamethicin (Schwarz & Savko, 1982;Yantorno, Takashima & Mueller, 1982) and trichotoxin A40 (Schwarz, Savko & Jung, 1983). Elementary dipoles originate from the charge separation phenomenon at peptide bonds (Hol et al, 1978) and sum up to macrodipoles in case of rods of helical structure (Hol, Halie & Sander, 1981;Hol, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the insertion of helical polypeptides into lipid bilayers is mainly determined by the electric field within the membrane as well as by electrostatic interaction between the dipolar molecules themselves. Added to one side of the bilayer, helical rods Such a mechanism has been proposed for alamethicin , which exhibits a large intrinsic dipole moment (Schwarz & Savko, 1982;Yantorno et al, 1982). If polypeptides are added to both sides of a planar bilayer, the spontaneous establishment of larger aggregates of antiparallel oriented dimers seems to be energetically favored.…”
Section: Weakly Voltage-dependent Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…5 It has been suggested that the alamethicin monomer is about 3.5 nm in length and carries a dipole moment of approximately 75 D units, which is responsible for the voltage- dependent conductance. 6,7 We can conclude that the QDs, having a permanent dipole moment 8 similar to alamethicin, are influenced by an external electric field, which creates a torque on the QD dipole, forcing insertion into the lipid membrane ͓Fig. 1͑a͔͒.…”
Section: ͑23°c͒mentioning
confidence: 99%
“…In the case of Alm this behaviour is best explained in terms of re-orientation of the helix dipole (Hole et al 1978;Schwarz and Savko 1982) in the imposed electric field (Boheim et al 1983;Mathew and Balaram 1983;Sansom 1991). The negatively charged residue near the C-terminus (El8) is believed to anchor the C-terminus at the bilayer-water interface, and thus only when a cis positive potential is applied is the helix able to reorient itself in the bilayer, by repulsion of the formal positive charge (+ 1/2) at the N-terminus.…”
Section: ) Voltage Activationmentioning
confidence: 99%